PENGARUH PENGENDALIAN INTERNAL PERSEDIAAN DAN SISTEM INFORMASI AKUNTANSI TERHADAP UPAYA PENCEGAHAN KECURANGAN (FRAUD) DALAM PENGELOLAAN PERSEDIAAN PADA PT MITRA JAMBI PRATAMA - Mufidah Mufidah (Jurnal Ilmiah Universitas Batanghari Jambi, 2017)
This research aims to analyze: (1) influence of internal controls against fraud prevention on inventory management of inventory in PT Mitra Jambi Pratama. (2) to analyse the influence of the accounting information system towards the prevention of fraud in the management of the inventory of PT. Mitra Jambi Pratama. Analysis using Partial Least Square (PLS), start from measurement model (outer model), model structure (inner models) and hypothesis testing. The results showed that (1) the internal control supplies has positive significant affect  to the prevention of fraud in the management of supplies in PT. Mitra Jambi Pratama and (2) the accounting information system  has positive significant   affect to the prevention of fraud on inventory management on PT. Mitra Jambi PratamaKeywords: Internal control ,  information systems, Fraud